Suffering in Mu'tazilite Theology : 'Abd al-Jabbār's Teaching on Pain and Divine Justice - Heemskerk (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
'Abd al-Ğabbār (d. 1024 AD) belonged to the Bahšamiyya branch of the Basra Mu'tazila. The Mu'tazilites upheld the principle of divine justice, and from this perspective they attempted to explain the existence of pain and suffering. This volume deals with 'Abd al-Ğabbār's opinions on different aspects of pain, such as what pain is, how it is perceived, how it comes into existence, how to judge the infliction of pain and for which purpose God imposes suffering on His creatures. Attention is also given to opinions expressed by Mānkdīm and Ibn Mattawayh, disciples of 'Abd al-Ğabbār. Included is a historical survey of the Bahšamiyya school. The book sheds light on 'Abd al-Ğabbār's Mu'tazilite method in dealing with the question of the existence of human suffering.